Computing scores of voice quality and speech intelligibility in tracheoesophageal speech for speech stimuli of varying lengths. (May 2016) - Clapham, Renee P.; Martens, Jean-Pierre; van Son, Rob J.J.H.; Hilgers, Frans J.M.; van den Brekel, Michiel M.W.; Middag, Catherine
Abstract : Highlights: Study investigates speech length and phonetic variety on model performance. Introduce strategy comparing models with restricted and non-restricted feature inputs. No statistical difference in model performance when feature inputs are restricted. Speech material circa 100 syllables allows accurate and stable model evaluation. Abstract: In this paper, automatic assessment models are developed for two perceptual variables: speech intelligibility and voice quality. The models are developed and tested on a corpus of Dutch tracheoesophageal (TE) speakers. In this corpus, each speaker read a text passage of approximately 300 syllables and two speech therapists provided consensus scores for the two perceptual variables. Model accuracy and stability are investigated as a function of the amount of speech that is made available for speaker assessment (clinical setting). Five sets of automatically generated acoustic-phonetic speaker features are employed as model inputs. In Part I, models taking complete feature sets as inputs are compared to models taking only the features which are expected to have sufficient support in the speech available for assessment. In Part II, the impact of phonetic content and stimulus length on the computer-generated scores is investigated. Our general finding is that a text encompassing circa 100 syllables is long enough to achieve close to asymptotic accuracy.